Burrow charaderistics and habitat assodations of armadillos in Brazil and the United States of America - McDonough, Colleen M (Universidad de Costa Rica, 2000)
We censused and measured armadillo burrows in ten 10 m x 40 m plots in each of four habitat types at a study site in northern Florida and one in the Atlantic coastal rainforest of Brazi!. The nine-banded armadillo (Dasypus novemcinctus) was the only species of armadillo found in Florida, but several additional species were present in Brazil. Burrows were more numerous but smaller in Brazil than in the U. S., probably due to the inelusion of burrows dug by the smaller congener D. septemcinctus. In Brazil, burrows were larger and more numerous in swamp and forest habitats than in grass)and or disturbed areas, suggestíng that D. novemcinctus is found primarily in forests and swamps while D. septemcinctus is located in the other areas. This was supported by data from sightíngs of live animals. In Florida, burrows were more numerous in hardwood hammocks than in wetlands, fields or upland pine areas, but burrow dimensions did not vary across habitat types. In Florida, armadillos were seen more frequently than expected in hammocks and wetlands and less frequently thlll1 expected in fields and upland pine areas. There were also age (juvenile versus adult), sex, and yearly differences in habita! use in Florida. Biomass, abundance, and species diversity of terrestrial invertebrates did not vary significantly between habitat types in Florida, suggestíng that habitat associatíons of armadillos were not influenced by prey availability.